Anti-inflammatory effects of a methanol extract of Dictamnus dasycarpus Turcz. root bark on imiquimod-induced psoriasis - Minjee Choi; Jun Koo Yi; Si-Yong Kim; Jung Hyun Ryu; Jinhee Lee; Wookbong Kwon; Soyoung Jang; Dongjun Kim; MyoungOk Kim; Hyungwoo Kim; Sung Hyun Kim; Seong-Kyoon Choi; et al. (BMC, 2019)
Abstract Background The root bark of Dictamnus dasycarpus Turcz. has been successfully used for the treatment of inflammatory skin conditions such as eczema and pruritus. However, the anti-psoriatic effect of this plant has not until now been investigated. Methods The aim of this project was to investigate whether a methanol extract of Dictamnus dasycarpus Turcz. root bark (MEDD) can be used as a therapeutic agent for psoriasis in C57BL/6 mice model of imiquimod (IMQ)-induced psoriasis. IMQ and MEDD was applied to mouse skin continuously for 7 days. The skin phenotype and the levels of inflammatory cytokines, such as interferon (IFN)-γ and interleukin (IL)-17, were analyzed. The immune cell population was determined by flow cytometry, and STAT1 and 3 protein levels were measured. Results An alleviation of scaly skin phenotype, immune cell infiltration in the dermis, and epidermal hyperplasia was observed after daily MEDD treatment in the lesion-affected area. It was also found that MEDD reduced IL-17 cytokine levels decreased by 44.37% (p < 0.05), the number of IL-17-producing Th17 cells and γδT cells, and the size of the Th1 population secreting IFN-γ decreased by 45.98, 62.21, and 44.42%, respectively (p < 0.05), compared with the vehicle control group. STAT3 signals, associated with IL-17 are also reduced by MEDD. Conclusions An anti-psoriatic effect of MEDD was observed, as determined by decreased skin inflammation, reduced number of inflammatory cytokines, and a smaller population of inflammatory cells. These results contribute to the validation of the use of MEDD in the treatment of psoriasis.